Ability to assess the credibility of news in students of social communication at a University of Peru - Peceros García, Fabrizio (2021)
The objective of this research was to evaluate the capacity of the students of social communication of the Universidad Nacional Mayor de San Marcos to evaluate the credibility of news; likewise, as a specific objective it is to evaluate their capacity by means of the variable sex, level of study and specialty of the career. About the method, it was of quantitative cut, descriptive reach, non-experimental design and of transversal type, two news were used for the investigation, one false and other real. The CRAAP test was used as an instrument for data collection, which has criteria related to the analysis of information. In the results, it was obtained that the students' capacity to identify news is regularly acceptable (47.5%), the average was higher in true news (33.49) than in false news (28.82); differences were found in the averages according to sex (female 31.69 and male 30.57, level of studies (basic 29.27, intermediate 30.37, advanced 32.09), according to studies with specialty (31.57) and general studies (29.27). In conclusion, students of social communication present regularly acceptable capacity to evaluate the credibility of the news, being able to differentiate a true news from a false one, but they present complications during the process.